Blockchain for business : discover how blockchain networks are transforming companies, driving growth, and creating new business models - Arun, Jai Singh; Cuomo, Gennaro; Gaur, Nitin (Addison-Wesley : Pearson Education, 2019)
The Pragmatic Guide to Driving Value and Disrupting Markets with Blockchain "Much has been written about blockchain in the past few years: what it is and what it is not (at various levels of detail), as well as the technology's long-term strategic value for companies, industries, and economies. However, what we've been missing is a practical, operational, 'how to' set of steps for creating, implementing, and operating a blockchain-based solution. This book aims to fill that gap. It's an invaluable tool for anyone ready to take the plunge and start taking advantage of this remarkable technology.' -Irving Wladawsky-Berger, research affiliate, MIT; columnist, WSJ CIO Journal; VP Emeritus, IBM Blockchain enables enterprises to reinvent processes and business models and to pursue radically disruptive applications. Blockchain for Business is a concise, accessible, and pragmatic guide to both the technology and the opportunities it creates. Authored by three experts from IBM's Enterprise Blockchain practice, it introduces industry-specific and cross-industry use cases, and reviews best-practice approaches to planning and delivering blockchain projects. With a relentless focus on real-world business outcomes, the authors reveal what blockchain can do, what it can't do yet, and where it's headed. Understand five elements that make blockchain so disruptive: transparency, immutability, security, consensus, and smart contracts Explore key use cases: cross-border payments, food and drug safety, provenance, trade finance, clinical trials, land registries, and more See how trusted blockchain networks are facilitating entirely new business models Compare blockchain types: permissioned, permissionless, private, public, federated, and hybrid Anticipate key technical, business, regulatory, and governance challenges Build blockchain financial models, investment rubrics, and risk frameworks Organize and manage teams to transform blockchain plans into reality Whether you're a senior decision maker, technical professional, customer, or investor, Blockchain for Business will help you cut through the hype and objectively assess blockchain's potential in your business. Register your product for convenient access to downloads, updates, and/or corrections as they become available